Intraoperative Anesthetic Management for Vascular and Endovascular Abdominal Aortic Surgery - Estruch-Perez, Maria J.; Balaguer-Domenech, Josep; Plaza-Martinez, Angel; Solaz-Roldan, Cristina (IntechOpen, 2012)
None